Efficacy Of Yogic Practices On Systolic And Diastolic Blood Pressure Among Migraine Sufferers (Journal of Pharmaceutical Negative Results, 2023)
To facilitate the random group experimental study, 90 Men suffering with Migraine between 35 to 45 years of Age were invited, 60 screened and selected finally in random as subjects by using random group sampling design. Subjects were divided into two groups of 20 each. Yoga therapy was imparted for 12 weeks to the experimental and control kept in active rest The pre-test and post-test were conducted before and after the training for the experimental and control group and the scores on Diastolic and Systolic Blood Pressure were measured. Analysis of covariance (ANCOVA) was used to find out the significant differences among the groups. The result of the study showed that Diastolic and Systolic Blood Pressure significantly reduced as a result of Yogic practices in the Experimental Group. Hence the hypothesis was accepted at 0.05 level of confidence. The conclusion was that the Yogic practices helped reduce Diastolic and Systolic Blood Pressure among Men suffering with Migraine.